Relationship between the occurrence of the rice water weevil and water depth in flooded rice crop - Büttow, Germano Tessmer; Pazini, Juliano de Bastos; Seidel, Enio Júnior; da Silva, Fernando Felisberto; Grützmacher, Anderson Dionei; Martins, José Francisco da Silva (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to assess the relationship between the depth of irrigation water and larval infestation by Oryzophagus oryzae in flooded rice crop. Water depth and larval infestation were evaluated in the upper levee, in between levees, and in the lower levee. The data were subjected to the descriptive statistical and geostatistical analyses. The highest larval infestation occurs in field areas with greater water depth, which is typical of the lower levee. The spatial distribution of O. oryzae larvae is of the aggregate type and depends on the greater irrigation water depth.